Determination of effective elastic properties of ferritic ductile cast iron by computational homogenization, micrographs and microindentation tests - Fernandino, Diego Omar (2015)
A comprehensive procedure for the prediction of the elastic behavior of ferritic ductile iron by means of multiscale analysis is introduced in this work. The procedure combines computational procedures for the homogenization analysis, micrographic analysis to retrieve the geometries for the finite element analysis, and microindentation tests to assess the elastic behaviors of the different phases of the microstructure. The size of the representative volume element (RVE) is assessed in terms of geometrical descriptors of the microstructure (graphite fraction and nodule count and size) and the invariance and isotropy of the homogenized elastic responses. The RVE is sized to contain at least 50 nodules, and it results from 100× micrographs. The results for the homogenized values for the Young?s modulus and the Poisson`s ratio are found in excellent agreement to the data retrieved from tensile tests, values reported in the bibliography and analytical formulas available in the literature. The proposed procedure can be easily extended to the characterization of cast irons with more complex microstructures.